ANALYSIS OF HYPERCHOLESTEROLEMIA PREVALENCE IN THE OUTPATIENT PRACTICE (ACCORDING TO THE ARGO STUDY): PART I - N. M. Akhmedzhanov; D. V. Nebieridze; A. S. Safaryan; V. A. Vygodin; A. Yu. Shuraev; O. N. Tkacheva; A. S. Lishuta (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the level of total cholesterol in patients at high and very high cardiovascular risk in real clinical practice and the correspondence of their follow-up to current guidelines for the treatment of dyslipidemia issued by European Society of Cardiology and European Atherosclerosis Society (2011), as well as Russian Society of Cardiology and Russian National Society of Atherosclerosis (2012).Material and methods. Patients aged 30 years and older who visited a general practitioner or a cardiologist in an outpatient clinic in the period from October 2013 to July 2014 were included into the study. Every patient filled out a special questionnaire. The total cholesterol measurement was performed without special preparation of the patient with portable photometric blood analyzer, which allows the evaluation of total cholesterol in 3 minutes.Results. 18.273 patients (58.9% women) were included in the final analysis. Hypercholesterolemia was found in 81.3% women and 78.9% males. In all federal districts the total cholesterol level was significantly above the target and varied from 5.82 to 6.10 mmol/L. At that, statins had not been prescribed to almost half of the patients. Total cholesterol> 5 mmol/L was found in 84.7% of the patients treated with simvastatin, in 75.2% of the patients treated with atorvastatin, in 59% of the patients treated with rosuvastatin. Target level of total cholesterol (<4 mmol/L) was achieved in 2.04-7.38% of the patients at a very high cardiovascular risk.Conclusion. The situation with the diagnosis and treatment of dyslipidemias in a real clinical practice is far from perfect, despite the availability of information for doctors and patients. The causes of this problem require further investigation.